2023
DOI: 10.1039/d3qo00232b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-amino acid derived (1,2,3-triazol-4-yl)-picolinamide (tzpa) ligands and their corresponding luminescent Tb(iii) complexes

Abstract: The synthesis of chiral α-amino acid derived (1,2,3-triazol-4-yl)-picolinamide (tzpa) ligands 4-6 designed by combining the coordination properties of two well-known ligand structures within a single unit is described. The self-assembly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…This diversity is valuable for creating peptides with specific 205 with permission from Royal Society of Chemistry, copyright 2023). 205 chemical, electronic, or steric characteristics. The Gunnlaugsson group elegantly exploited this idea with their recent publication detailing the synthesis of chiral α-amino acid derived ligands for Ln 3+ luminescence.…”
Section: Lanthanide-based Peptide Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…This diversity is valuable for creating peptides with specific 205 with permission from Royal Society of Chemistry, copyright 2023). 205 chemical, electronic, or steric characteristics. The Gunnlaugsson group elegantly exploited this idea with their recent publication detailing the synthesis of chiral α-amino acid derived ligands for Ln 3+ luminescence.…”
Section: Lanthanide-based Peptide Probesmentioning
confidence: 99%
“…The Gunnlaugsson group elegantly exploited this idea with their recent publication detailing the synthesis of chiral α-amino acid derived ligands for Ln 3+ luminescence. 205 These novel ligands contained l -phenylalanine and l -tryptophan – as their methyl esters – which underwent supramolecular self-assembly to form 1 : 3 complexes with Tb 3+ under thermodynamic control. Indeed, both complexes were able to evoke Tb 3+ -centred emission ( λ ex = 255 nm).…”
Section: Convergence Of Therapeutics and Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this strategy, enantiomer pairs of Eu 3+ complexes for both the i Pr and Ph-PyBox derivatives were synthesized (Scheme ). On one hand, PyBox ligands have shown to be suitable chirality inducers in both homo- and heteroleptic complexes. On the other hand, Maury et al showed that the strategy of ligands with extended conjugation and strong push–pull systems with varying charge-transfer character provides high 2PE cross sections in the case of dipicolinic acid derivatives. ,, …”
Section: Introductionmentioning
confidence: 99%
“… 36 43 On the other hand, Maury et al showed that the strategy of ligands with extended conjugation and strong push–pull systems with varying charge-transfer character provides high 2PE cross sections in the case of dipicolinic acid derivatives. 31 , 32 , 44 54 …”
Section: Introductionmentioning
confidence: 99%